Long-term impact of stroke on patients' health-related quality of life. Issue 14 (3rd July 2017) - De Wit, Liesbet; Theuns, Peter; Dejaeger, Eddy; Devos, Stefanie; Gantenbein, Andreas R.; Kerckhofs, Eric; Schuback, Birgit; Schupp, Wilfried; Putman, Koen
Abstract: Purpose: This international study aims to examine the size and determinants of the impact of stroke on five-year survivors' health-related quality of life (HRQoL) in four different European countries. Method: Patients were recruited consecutively in four European rehabilitation centers. Five years after stroke, the EuroQol-visual analog scale (EQ-VAS) was administered in 226 first-ever stroke patients. Impact of stroke was determined by calculating EQ-VAS z -norm scores (= deviation – expressed in SD – of patients' EQ-VAS level relative to their age-and gender-matched national population norms). Determinants of EQ-VAS z -norm scores were identified using multivariate linear regression analysis. Results: Five years post-stroke, patients' mean EQ-VAS was 63.74 ( SD = 19.33). Mean EQ-VAS z -norm score was −0.57 [95%CI: (−0.70)–(−0.42)]. Forty percent of the patients had an EQ-VAS z- norm score <−0.75 SD ; 52% had an EQ-VAS z -norm score between −0.75 and +0.75 SD, only 8% scored >+0.75 SD . Higher patients' levels of depression, anxiety and disability were associated with increasingly negative EQ-VAS z -norm scores (adjusted R 2 = 0.392). Conclusions: Five years after stroke, mean HRQoL of stroke survivors showed large variability and was more than ½ SD below population norm. Forty percent had a HRQoL level below, 52% on, and 8% above population norm. The variability could only partially be explained by the variables considered in this study. Longitudinal studies are needed to increase our understanding of the size and determinants of the impact of stroke on the HRQoL of long-term stroke survivors. Implications for rehabilitation: The current European concept of stroke rehabilitation is focused on the acute and sub-acute rehabilitation phase, i.e., in the first months after stroke. The results of this study show that at five years after stroke, the mean level of HRQoL of stroke survivors remains below the healthy population level. This finding shows the need for continuation of rehabilitation in the chronic phase. At five years after stroke, higher patients' levels of depression, anxiety and disability were associated with lower scores for HRQoL. This finding implicates that chronic rehabilitation programs should be multi-faceted in order to increase long-term survivors' psychosocial outcomes.